RISK FACTORS OF HIV-1 VERTICAL TRANSMISSION (VT) AND THE INFLUENCE OF ANTIRETROVIRAL THERAPY (ART) IN PREGNANCY OUTCOME - Barral, Maria F.M.; Oliveira, Gisele R. de; Lobato, Rubens C.; Mendoza-Sassi, Raul A.; Martinez, Ana M.b.; Goncalves, Carla V. (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
In the absence of intervention, the rate of vertical transmission of HIV can range from 15-45%. With the inclusion of antiretroviral drugs during pregnancy and the choice of delivery route this amounts to less than 2%. However ARV use during pregnancy has generated several questions regarding the adverse effects of the gestational and neonatal outcome. This study aims to analyze the risk factors for vertical transmission of HIV-1 seropositive pregnant women living in Rio Grande and the influence of the use of ARVs in pregnancy outcome. Among the 262 pregnant women studied the rate of vertical transmission of HIV was found to be 3.8%. Regarding the VT, there was a lower risk of transmission when antiretroviral drugs were used and prenatal care was conducted at the referral service. However, the use of ART did not influence the outcome of pregnancy. However, initiation of prenatal care after the first trimester had an influence on low birth weight, as well as performance of less than six visits increased the risk of prematurity. Therefore, the risk factors analyzed in this study appear to be related to the realization of inadequate pre-natal and maternal behavior.